Pengendalian Internal Penerimaan Negara Bukan Pajak di Taman Nasional Bali Barat - Rakhmah Budi; Nur Handayani (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
This study aims to know the internal control of non-tax state revenues in Bali Barat National Park in terms of accuracy of recording, staffing, and the effectiveness of non-tax state revenue policy in Bali Barat National Park. This research is qualitative descriptive research. The method of analysis used in this research is triangulation technique. Based on the results of the study, it can be taken several provisions of Government Regulation No. 12 of 2014 to become a tool of internal control of non-tax state revenue in Bali Barat National Park. The accuracy of recording of non-tax state revenue in Bali Barat National Park at the tariff level based on Government Regulation No. 12 of 2014 on Tariff of Non-Tax State Revenue applicable to the Ministry of Forestry. For Non-Tax State Revenue Receiver in Bali Barat National Park on Government Regulation No. 20/1997 on Non-Tax State Revenues. Then for the level of effectiveness of Non-Tax State Revenue in Bali Barat National Park, with the title effectiveness above 100% in every year, not the standard in Bali Barat National Park is very effective. Keywords: Internal control, Non-Tax State Revenue, and Management of government finances